WhatsApp assessment for communication and organization of group work in resident physicians: Valoración de WhatsApp para la comunicación y organización del trabajo grupal en médicos residentes - Villar Meza, Luisa E. (2021)
Introduction: New communication technologies allow new opportunities to optimize medical work. Objective: To determine the assessment of WhatsApp for communication and organization of group work among resident physicians during a healthcare management course. Methods: Descriptive, prospective, cross-sectional study. The population consisted of 140 resident physicians who participated in a healthcare management course in 2019 and 2020. A non-probability convenience sample of 132 participants was obtained. We applied the instrument to assess WhatsApp for regulating group work, through the dimensions “WhatsApp for organizing group work” and “WhatsApp as a communication system for group work”, with a reliability of 0.92. Based on the scores assigned to this dimension by the participants, we divided them into three groups: low, medium and high rating. Results: Resident physicians from eight specialties participated: psychiatry, internal medicine, otolaryngology, clinical pathology, cardiovascular surgery, anatomic pathology, legal medicine and pediatric ophthalmology. The average age was 33.37 years. 86.4% of residents use WhatsApp daily. Activity planning and sending text messages and brief instructions had favorable scores. Both dimensions scored 47.36% in the low rating group, 46.35% in the high rating group and 39.3% in the medium rating group. The global result showed a predominance of the high and low rating groups. Conclusion: The majority of resident physicians use WhatsApp as a non-formal communication tool, helpful for sending messages, developing group tasks and planning activities. Additionally, resident physicians and professors consider WhatsApp to be a useful app, and it could facilitate knowledge acquisition.